Targeted therapy in ovarian cancer – at what point are we? - Kaczmarek-Borowska, Bożenna; Trelińska-Nowosad, Teresa; Karolewski, Kazimierz; Jóźwik, Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
The basic, conventional methods of anticancer therapy, such as chemotherapy or radiotherapy, are not sufficient in many cases because of poor response and adverse effects observed afterwards. Effective anticancer drugs should recognize tumour cells and selectively eliminate them without damaging healthy tissue. Such therapy, described as targeted therapy, is directed against epidermal growth factor receptor and vascular endothelial growth factor receptor. Among drugs that act in such a way there are monoclonal antibodies that block extracellular receptors or their ligands, and tyrosine kinase inhibitors influencing the intracellular domain of receptors. To date few randomized clinical trials with targeted therapy in ovarian cancer have been performed. The most common examined drugs include: bevacizumab, trastuzumab, gefitinib, erlotinib and cetuximab. Many drugs show some activity in ovarian cancer patients, but prolonged periods of disease stabilisation rather than response to the therapy is observed. Studies of ovarian cancer patients in early stages showed that combination of chemotherapy and targeted therapy drugs was justified, although therapy schedules including new drugs in combination with the most effective chemotherapy schedules should be tested in large randomized trials.